2001
DOI: 10.1073/pnas.091018698
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of the vitamin D receptor complexed to superagonist 20-epi ligands

Abstract: The crystal structures of the ligand-binding domain (LBD) of the vitamin D receptor complexed to 1␣,25(OH)2D3 and the 20-epi analogs, MC1288 and KH1060, show that the protein conformation is identical, conferring a general character to the observation first made for retinoic acid receptor (RAR) that, for a given LBD, the agonist conformation is unique, the ligands adapting to the binding pocket. In all complexes, the A-to D-ring moieties of the ligands adopt the same conformation and form identical contacts wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
198
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(213 citation statements)
references
References 33 publications
12
198
2
1
Order By: Relevance
“…Like the x-ray crystal structures of VDR superagonists [14] and 1,25D [11], the recently solved KH-VDR (VDR from zebrafish) complex [12] clearly demonstrates that the ligand binding pocket adapts to the KH sterol so it stabilizes the closed VDR H12 conformation (hVDR-c1). The KH-VDR x-ray result does correlate well with its ability to transactivate with similar or greater efficacy relative to 1,25D; however, the structure does not correlate with KH's solution state PSA results or reduced VDR affinity [18].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Like the x-ray crystal structures of VDR superagonists [14] and 1,25D [11], the recently solved KH-VDR (VDR from zebrafish) complex [12] clearly demonstrates that the ligand binding pocket adapts to the KH sterol so it stabilizes the closed VDR H12 conformation (hVDR-c1). The KH-VDR x-ray result does correlate well with its ability to transactivate with similar or greater efficacy relative to 1,25D; however, the structure does not correlate with KH's solution state PSA results or reduced VDR affinity [18].…”
Section: Introductionmentioning
confidence: 84%
“…1C, yellow circles). Residues N424, E425, I426, and S427 are unresolved in the 1,25D-VDR x-ray structures [11,12,13,14,15], but when added in an α-helical orientation to the x-ray construct (pdb code: 1DB1), prior to assembly minimization, it was observed that R402 (H11) formed Coulombic interactions with either E425 and S398 or S427 and S398 (see methods; Fig. 1C, pink ribbon in yellow circle).…”
Section: Intramolecular Electrostatic Stabilization Of the C-terminalmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucial to 1,25D-hVDR Transactivation-Based on the hVDR x-ray crystallographic results (5,(25)(26)(27) His-305 and His-397 form hydrogen bonds (H-bonds) with the 25-OH group of 1,25D (28,29) (Fig. 2).…”
Section: Vdw Contacts Made With Helix-3 and Helix-12 Residues Arementioning
confidence: 99%
“…Our proposed A-pocket accepts ligands that differ in shape from those in the classical G pocket (3,23,24).…”
mentioning
confidence: 99%